2013
DOI: 10.1093/infdis/jit043
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antiretroviral Exposure and Renal Impairment Among HIV-Positive Persons With Normal Baseline Renal Function: the D:A:D Studya

Abstract: Tenofovir, ritonavir-boosted atazanavir, and ritonavir-boosted lopinavir use were independent predictors of chronic renal impairment in HIV-positive persons without preexisting renal impairment. Increased tenofovir discontinuation rates with decreasing eGFR may have prevented further deteriorations. After discontinuation, the ARV-associated incidence rates decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
224
8
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(264 citation statements)
references
References 46 publications
23
224
8
9
Order By: Relevance
“…Interestingly, these previous data also supported a strong association between CVD and renal function, which significantly diminished after accounting for other risk factors, suggesting an underlying biological mechanism at least partly mediated by other factors. We have also previously showed an association between the use of certain antiretroviral drugs and CVD and renal impairment [28,30,32]. The results of this analysis are entirely consistent with these prior findings, and adjustment for the use of individual antiretroviral drugs did not have any major impact on the association between impaired eGFR and CVD.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, these previous data also supported a strong association between CVD and renal function, which significantly diminished after accounting for other risk factors, suggesting an underlying biological mechanism at least partly mediated by other factors. We have also previously showed an association between the use of certain antiretroviral drugs and CVD and renal impairment [28,30,32]. The results of this analysis are entirely consistent with these prior findings, and adjustment for the use of individual antiretroviral drugs did not have any major impact on the association between impaired eGFR and CVD.…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies from D:A:D, we investigated the inverse relation between CVD events and eGFR, focusing on CVD as a risk factor for various levels of chronic renal impairment [28,29,31]. Interestingly, these previous data also supported a strong association between CVD and renal function, which significantly diminished after accounting for other risk factors, suggesting an underlying biological mechanism at least partly mediated by other factors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, this bias could explain another significant limitation of our work, which is the higher prevalence of boosted protease inhibitor (PI) as part of the ART regimen in TDF group patients. Boosted PIs have been related to a higher incidence of kidney disease in many observational studies [10,22], although data from clinical trials suggest a reasonable renal safety profile [23]. In our study, the use of PIs did not show any significant relationship with CRDRF so its role as a potential confounder in our study might be limited.…”
Section: Discussioncontrasting
confidence: 60%
“…Moreover, large clinical trials with long follow-up periods of more than 144 weeks in naïve patients have shown a renal safety profile of ART containing TDF, either similar to other ART without it, or with small significant declines in the estimated glomerular filtration rate (eGFR) of clinical implications difficult to ascertain [7][8][9]. Observational studies with longer follow-up periods suggest a more deleterious effect on the renal function, and point that TDF is associated with a higher incidence of chronic kidney disease [10][11][12][13][14][15][16][17]. Overall, these results have shown either a modest or absent decline in renal function associated with TDF use after short follow-up periods of months or very few years, while studies with longer follow-up periods suggest a more relevant decrease in renal function [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%